2000
DOI: 10.1143/jjap.39.l200
|View full text |Cite
|
Sign up to set email alerts
|

Hardness of Bulk Single-Crystal Gallium Nitride at High Temperatures

Abstract: The hardness of single-crystal gallium nitride at elevated temperatures is measured and compared with that of other semiconductors. A Vickers indentation method was used to determine the hardness under an applied load of 0.5 N in the temperature range 20-1200 • C. The average hardness was measured as 10.8 GPa at room temperature, which is comparable to that of Si. At elevated temperatures, GaN shows higher hardness than Si and GaAs. A high mechanical stability for GaN is deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…We first estimate the where a = 1 refers to the slip system oriented at 45 deg to the load ing direction and a = 2 and a = 3 are the slip systems oriented 60 deg in either direction from the a = 1 slip system, with slip planes aligned with a2 and a i in Fig. (17). For the optimal parameters listed in Table 2 and assuming the power law in Eq.…”
Section: Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…We first estimate the where a = 1 refers to the slip system oriented at 45 deg to the load ing direction and a = 2 and a = 3 are the slip systems oriented 60 deg in either direction from the a = 1 slip system, with slip planes aligned with a2 and a i in Fig. (17). For the optimal parameters listed in Table 2 and assuming the power law in Eq.…”
Section: Model Parametersmentioning
confidence: 99%
“…The plastic behavior of GaN films has been studied primarily through indentation tests [15][16][17], However, indentation tests are difficult to interpret because they produce a complex stress field below the indenter and induce slip on multiple slip sys tems [18]. The plastic behavior of GaN films has been studied primarily through indentation tests [15][16][17], However, indentation tests are difficult to interpret because they produce a complex stress field below the indenter and induce slip on multiple slip sys tems [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fewer pits observed probably originate from the threading dislocation created during GaN growth and open up or became visible during CMP. The opening up of the dislocations due to the chemical etching effect during CMP is well known as observed in other investigations [28,44,45]. Regarding occasional scratches found after CMP using optimum condition, it is owing to mechanical abrasion by relatively harder Al 2 O 3 particles.…”
Section: Resultsmentioning
confidence: 52%
“…The role of abrasion is expected to be less at higher temperature (≤30 ml/min flow rate in this study) since removal rate mechanism is predominantly chemical-kinetics dependent and hence material removal rate is relatively less. 35,36 The reaction product, Ga 2 O 3 , may further dissolve in the acidic (pH −2) slurry and subsequently gets abraded by the mechanical action of polishing in presence of hard abrasive Al 2 O 3 (Knoop microhardness of Al 2 O 3 : ∼20 GPa > GaN (∼10.8 GPa) 37 and Ga 2 O 3 ). 21,34,38 It has been reported that the increase in slurry (H 2 O 2 + Al 2 O 3 /CeO 2 ) flow rate up to a certain extent promotes the polishing rate of Si surfaces regardless of the type of abrasive particles.…”
Section: Resultsmentioning
confidence: 99%